(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2023)
In the article, we intend to describe the relationship between religiosity and empathy within the context of theory and contemporary research, through the psycho-pedagogical lens. The empirical stage of the study aims to ascertain the type of bond that young Polish religious adults have with God and determine the relationship between the bond and self-reported empathy. The Questionnaire of Attachment to God, designed by Matys and Bartczuk, was employed in this research. Empathy was measured using SSIE, a shortened version of the Empathy Quotient Scale. The study revealed that the perception of a relationship with God, defined by trust and security, correlates with empathy, while an approach to religion based on fear of God does not affect perceiving oneself as an empathic person. The article ends with a list of interventions that pastors and teachers can implement to increase young people’s connection to God and their capacity for empathy.